(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Several e-Democracy implementations started as an offshoot of e-Government implementation where other models of e-Government such as Government to Government (G2G), Government to Business (G2B), Government to Employees (G2E), and Government to NGOs (G2N) etc were first implemented before Government to Citizen (G2C). However, going by the resulting issues of lack of trust and apathy between Government and Citizen as well as the observed decline in votersâ€™ turnout for elections all over the world, a paradigm shift is hereby proposed in the design methodology starting from G2C to other models. This paper presents a framework for e-Democracy implementation that is premised on the e-Government development cube proposed by Rabaiah and Vandijck (2011), and Funikul and Chutimaskul (2009), which is based on fundamental platforms of organizational, infrastructural and institutional guidelines. Also, the incremental software engineering approach as described by Lizarralde et al. (2007) was employed for phased implementation of e-Government starting from e-Democracy (G2C); and a multi-channel approach, which includes Web 2.0, mobile devices and Internet that will enable a wider cross-section of the society to engage with e-Government was implemented. The deployment architecture of Evangelopoulos and Visinescu (2012) is employed. Essentially, the developed framework offers potentials for: increased participation and trust in the polity; reduced apathy between the electorate and the political class; and reduced intra and inter country politically motivated conflicts within the developed nations. Â